Facile solvothermal synthesis and functionalization of polyethylene glycol-coated paramagnetic Gd2(CO3)3 particles and corresponding Gd2O3 nanoparticles for use as MRI contrast agents - Dougherty, Atika (Elsevier, 2019)
Paramagnetic particles and nanoparticles have been widely used in bioimaging and biomedical applications. In this paper, functionalized gadolinium carbonate (Gd2(CO3)3) particles with polyethylene glycol (PEG) for use as an MRI contrast agent were produced. These PEGylated particles were also used as a single precursor for synthesizing Gd2O3 nanoparticles by a novel calcination pathway. The morphological, chemical, and structural properties of both the PEGylated Gd2(CO3)3 particles and Gd2O3 nanoparticles were examined using a scanning electron microscope (SEM), X-ray diffraction (XRD), Fourier transform infrared (FTIR), and energy dispersive X-ray spectroscopy (EDS) techniques. After the calcination process at a temperature of 800 C, the amorphous, rhombus flakes of PEGylated Gd2(CO3)3 were converted into crystalline nanospherical Gd2O3 particles with an average diameter of 80 nm. The hydrophilic polymer coating of PEG successfully attached to the Gd2(CO3)3 particles which resulted in high dispersibility and stability in a water based solution. The magnetic properties were investigated using a vibrating sample magnetometer (VSM), which showed that the PEGylated Gd2(CO3)3 and Gd2O3 exhibit paramagnetic character. Furthermore, in vitro magnetic resonance imaging (MRI) demonstrated that PEGylated Gd2(CO3)3 particles show a promising T1 weighted effect and could potentially serve as a T1 MRI contrast agent